Research on damage evolution of deep formation rock based on acoustic emission test. (January 2021) - Tian, Yong; Yu, Rangang; Zhang, Yin; Zhao, Xinbo
The study of rock damage evolution is of great significance in the field of underground engineering. In this paper, the damage development of deep formation rock was quantitatively evaluated by acoustic emission (AE) test. The Young's modulus of the test rock specimens under ideal intact state was obtained by assuming a linear relationship between the AE rate parameter and the damage variation based on the rate process theory. Through the multi-stage cyclic loading test, the damage parameters corresponding to the peak stress of the previous stage were calculated by using the tangent modulus at the initial moment. The results showed that there was abrupt transition stage of damage development with the linear increase of stress. The damage parameter curves of rock specimens during loading process were obtained by using the method of cumulative AE energy, and the development trend of the curves was analyzed simply by combining the concepts of crack initiation stress and crack damage stress. Comparing the two methods of obtaining damage parameters by using cyclic loading test and cumulative AE energy, the results of them were highly consistent except for some deviation in the initial and final stages.